Thermochromic resin composite material and laminate using same

A resin composite material with a sea-island structure and metal film adjusts light absorption and reflection based on temperature, addressing the absorption rate imbalance in conventional thermochromic materials, enabling efficient heat management.

JP7626109B2Active Publication Date: 2025-02-04KK TOYOTA CHUO KENKYUSHO
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022109911
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-07-07
Publication Date
2025-02-04
Estimated Expiration
2042-07-07

AI Technical Summary

Technical Problem

Conventional thermochromic materials exhibit low visible light absorption rates at high temperatures (e.g., 70 °C or higher) and high absorption rates at low temperatures (e.g., 40 °C or lower), limiting their practical applications.

Method used

A resin composite material comprising specific ratios of acrylic polymer, polyvinylidene chloride, and polycaprolactone, with black pigments or dyes, and optionally glass fillers, forming a sea-island structure that adjusts light absorption and reflection based on temperature, enhanced by a metal film.

Benefits of technology

The material achieves low visible light absorption at high temperatures and high absorption at low temperatures, allowing for effective temperature-dependent heat management.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626109000001
    Figure 0007626109000001
  • Figure 0007626109000002
    Figure 0007626109000002
  • Figure 0007626109000003
    Figure 0007626109000003
Patent Text Reader

Abstract

To provide a resin composite material that exhibits decreased visible light absorption at high temperatures (such as 70°C or above), while demonstrating increased visible light absorption at low temperatures (such as 40°C or below).SOLUTION: A thermochromic resin composition contains 15-84 mass% of an acrylic polymer, 15-84 mass% of polyvinylidene fluoride and 1-40 mass% of polycaprolactone. A thermochromic resin composite material contains, based on 100 pts.mass of the thermochromic resin composition, 0.0005-0.03 pt.mass of at least one kind of a black colorant selected from a group consisting of black pigments and black dyes.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermochromic resin composite material and a laminate using the same. [Background technology]

[0002] In recent years, thermochromic materials that change color or transparency depending on temperature have been attracting attention. For example, JP 2001-354952 A (Patent Document 1) discloses a thermochromic material obtained by adding a solution or dispersion in which a dye, an inorganic pigment, and / or an organic pigment is dissolved or dispersed in water or an organic solvent to an aqueous polymer solution and / or an aqueous hydrogel solution, and then concentrating the solution. However, since this thermochromic material contains water as a medium, it has been difficult to use it in a member in which the absorptance of visible light is low at high temperatures (e.g., 70°C or higher) and the absorptance of visible light is high at low temperatures (e.g., 40°C or lower). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2001-354952 A Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made in consideration of the problems associated with the above-mentioned conventional technologies, and aims to provide a resin composite material that exhibits low visible light absorptance at high temperatures (e.g., 70°C or higher) and high visible light absorptance at low temperatures (e.g., 40°C or lower), as well as a composite material that exhibits high visible light reflectance at high temperatures (e.g., 70°C or higher) and low visible light reflectance at low temperatures (e.g., 40°C or lower). [Means for solving the problem]

[0005] As a result of intensive research to achieve the above-mentioned object, the inventors have discovered that a resin composition containing an acrylic polymer, polyvinylidene fluoride, and polycaprolactone in a specific ratio exhibits a thermochromic effect that improves transparency at high temperatures of 70°C or higher, and that a resin composite material in which this resin composition is blended with a black colorant exhibits low visible light absorptance at high temperatures of 70°C or higher and high visible light absorptance at low temperatures of 40°C or lower, and further that a laminate in which a metal film is provided on one side of a member made of this resin composite material exhibits high visible light reflectance at high temperatures of 70°C or higher and low visible light reflectance at low temperatures of 40°C or lower, thereby completing the present invention.

[0006] That is, the present invention provides the following aspects.

[0007] [1] Polymethylmethacrylate A thermochromic resin composite material comprising: a thermochromic resin composition containing 15 to 84 mass% of a polyvinylidene fluoride, 15 to 84 mass% of polyvinylidene fluoride, and 1 to 40 mass% of polycaprolactone; and 0.0005 to 0.03 mass parts of at least one black colorant selected from the group consisting of black pigments and black dyes, per 100 mass parts of the thermochromic resin composition.

[0008] [2] The thermochromic resin composite material according to [1], further comprising 50 parts by mass or less of a glass-based filler per 100 parts by mass of the thermochromic resin composition.

[0009] [3] The thermochromic resin composite material according to [2], wherein the glass-based filler has a silicon dioxide purity of 90% or more.

[0010] [4] The thermochromic resin composite material according to any one of [1] to [3], wherein the black colorant is carbon particles having a graphite structure.

[0011] [5] A laminate comprising a member made of the thermochromic resin composite material according to any one of [1] to [4], and a metal film having a visible light reflectance of 70% or more disposed on at least a portion of one side of the member.

[0012] Incidentally, the reason why the thermochromic resin composite material of the present invention has a low visible light absorptance at high temperatures of 70°C or higher and a high visible light absorptance at low temperatures of 40°C or lower, and why the laminate of the present invention has a high visible light reflectance at high temperatures of 70°C or higher and a low visible light reflectance at low temperatures of 40°C or lower, is not entirely clear, but the inventors speculate as follows.

[0013] That is, since polycaprolactone has a melting point of about 60°C, it forms a crystalline phase at a low temperature of 40°C or less. Therefore, when the thermochromic resin composite material of the present invention is exposed to a low temperature of 40°C or less, a sea-island structure is formed having a sea phase consisting of a polymer blend of an acrylic polymer and polyvinylidene fluoride and an island phase consisting of at least a part of polycaprolactone crystals. When visible light is irradiated to a thermochromic resin composite material having such a sea-island structure at a low temperature of 40°C or less, the incident visible light is scattered by the island phase, and the optical path length when propagating through the thermochromic resin composite material becomes long, so that the light is easily absorbed by the black colorant contained in the thermochromic resin composite material. As a result, it is presumed that the absorptance of visible light is high at a low temperature of 40°C or less. In addition, it is presumed that when visible light is irradiated to the laminate of the present invention at a low temperature of 40°C or less, the visible light is absorbed in the member consisting of the thermochromic resin composite material of the present invention, and the reflection of visible light by the metal film is reduced, resulting in a lower reflectance of visible light.

[0014] On the other hand, polycaprolactone melts at about 60°C, and therefore, at high temperatures of 70°C or higher, the crystals melt completely. Therefore, when the thermochromic resin composite material of the present invention is exposed to high temperatures of 70°C or higher, a sea-island structure is formed having a sea phase made of a polymer blend containing an acrylic polymer and polyvinylidene fluoride in a predetermined ratio and an island phase made of molten polycaprolactone. When visible light is irradiated to a thermochromic resin composite material having such a sea-island structure at high temperatures of 70°C or higher, the refractive index of the molten polycaprolactone matches the refractive index of the polymer blend containing an acrylic polymer and polyvinylidene fluoride in a predetermined ratio, so that scattering of the incident visible light is suppressed and the optical path length during propagation through the thermochromic resin composite material is shortened, so that the absorption of visible light by the black colorant contained in the thermochromic resin composite material is less likely to occur. As a result, it is presumed that the absorptance of visible light is reduced at high temperatures of 70°C or higher. Furthermore, when visible light is irradiated onto the laminate of the present invention at a high temperature of 70°C or higher, it is presumed that the visible light is less absorbed by the member made of the thermochromic resin composite material of the present invention and more visible light is reflected by the metal film, resulting in a high reflectance of visible light. Effect of the Invention

[0015] According to the present invention, it is possible to obtain a resin composite material that exhibits low visible light absorptance at high temperatures of 70° C. or higher and high visible light absorptance at low temperatures of 40° C. or lower. Furthermore, by providing a metal film on one side of a member made of such a resin composite material, it is possible to obtain a laminate that exhibits high visible light reflectance at high temperatures of 70° C. or higher and low visible light reflectance at low temperatures of 40° C. or lower. Furthermore, in such a laminate, it is possible to control the amount of heat generated by sunlight by changing the temperature. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be described in detail below based on preferred embodiments thereof.

[0017] [Thermochromic resin composite material] First, the thermochromic resin composite material of the present invention will be described. The thermochromic resin composite material of the present invention contains a thermochromic resin composition containing 15-84 mass% of an acrylic polymer, 15-84 mass% of polyvinylidene fluoride, and 1-40 mass% of polycaprolactone, and 0.0005-0.03 mass parts of at least one black colorant selected from the group consisting of black pigments and black dyes, relative to 100 mass parts of the thermochromic resin composition. In addition, the thermochromic resin composite material of the present invention preferably further contains 50 mass parts or less of a glass-based filler relative to 100 mass parts of the thermochromic resin composition.

[0018] (acrylic polymer) The acrylic polymer used in the present invention includes homopolymers and copolymers of acrylic monomers. The ratio of acrylic monomer units in the copolymer of acrylic monomers is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, and particularly preferably 90 mol% or more. Among these acrylic polymers, homopolymers of acrylic monomers are preferred from the viewpoints of excellent heat resistance and transparency, and low visible light absorption rate at high temperatures of 70°C or more in the obtained resin composite material.

[0019] Examples of the acrylic monomer include alkyl methacrylates (e.g., methyl methacrylate, ethyl methacrylate, etc.), alkyl acrylates (e.g., methyl acrylate, ethyl acrylate, etc.), methacrylic acid, and acrylic acid. Among these acrylic monomers, alkyl methacrylates are preferred, and methyl methacrylate is more preferred, from the viewpoint of excellent heat resistance and moldability.

[0020] Examples of other copolymerizable monomers in the copolymer of acrylic monomers include olefins (eg, ethylene, propylene, etc.) and aromatic vinyl monomers (eg, styrene, α-methylstyrene, etc.).

[0021] Specific examples of the acrylic polymer used in the present invention include polymethacrylic acid alkyl esters (e.g., polymethyl methacrylate, polyethyl methacrylate, etc.), polyacrylic acid alkyl esters (e.g., polymethyl acrylate, polyethyl acrylate, etc.), acrylic acid-methacrylic acid alkyl ester copolymers (e.g., acrylic acid-methyl methacrylate copolymers, etc.), methacrylic acid alkyl ester-acrylic acid alkyl ester copolymers (e.g., methyl methacrylate-ethyl acrylate copolymers, etc.), ethylene-methacrylic acid alkyl esters (e.g., ethylene-methyl methacrylate copolymers, etc.), ethylene-acrylic acid alkyl esters (e.g., ethylene-ethyl acrylate copolymers, etc.), styrene-methacrylic acid alkyl esters (e.g., styrene-methyl methacrylate copolymers, etc.), and styrene-acrylic acid alkyl esters (e.g., styrene-ethyl acrylate copolymers, etc.). Among these acrylic polymers, polymethacrylic acid alkyl esters are preferred, and polymethyl methacrylate is more preferred, from the viewpoints of excellent heat resistance and compatibility with polyvinylidene fluoride.

[0022] Moreover, the acrylic polymer used in the present invention preferably has a refractive index of 1.44 to 1.56, more preferably 1.46 to 1.56, even more preferably 1.46 to 1.54, and particularly preferably 1.47 to 1.51 at 60° C. If the refractive index of the acrylic polymer is less than the lower limit or exceeds the upper limit, the difference in refractive index from polycaprolactone becomes large, the transparency of the resulting resin composition at high temperatures of 70° C. or higher tends to decrease, and the visible light absorptance of the resulting resin composite material at high temperatures of 70° C. or higher tends to increase.

[0023] (Polyvinylidene fluoride) The polyvinylidene fluoride used in the present invention includes homopolymers and copolymers of vinylidene fluoride. The ratio of vinylidene fluoride units in the copolymer of vinylidene fluoride is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, and particularly preferably 90 mol% or more. Among such polyvinylidene fluorides, homopolymers of vinylidene fluoride are preferred from the viewpoint of excellent compatibility with the acrylic polymer (particularly polymethyl methacrylate).

[0024] Examples of other copolymerizable monomers in vinylidene fluoride copolymers include fluoroolefins (eg, trifluoroethylene, hexafluoropropylene, etc.) and aromatic vinyls (eg, styrene, α-methylstyrene, p-fluorostyrene, α-fluorostyrene, etc.).

[0025] Moreover, the polyvinylidene fluoride used in the present invention preferably has a refractive index of 1.36 to 1.47, more preferably 1.36 to 1.46, even more preferably 1.37 to 1.46, and particularly preferably 1.40 to 1.44 at 60° C. If the refractive index of the polyvinylidene fluoride is less than the lower limit or exceeds the upper limit, the difference in refractive index from polycaprolactone becomes large, the transparency of the resulting resin composition at high temperatures of 70° C. or higher tends to decrease, and the visible light absorptance of the resulting resin composite material at high temperatures of 70° C. or higher tends to increase.

[0026] (Polycaprolactone) The polycaprolactone used in the present invention is a ring-opening polymer of ε-caprolactone. Such a ring-opening polymer of ε-caprolactone may be a homopolymer of ε-caprolactone or a copolymer of ε-caprolactone and another monomer. The proportion of ε-caprolactone units in the copolymer of ε-caprolactone is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, and particularly preferably 90 mol% or more. Among such polycaprolactones, a homopolymer of ε-caprolactone is preferred from the viewpoints of excellent heat resistance, high opacity at low temperatures of 40°C or less in the obtained resin composition, and high visible light absorptance at low temperatures of 40°C or less in the obtained resin composite material.

[0027] Examples of other copolymerizable monomers in the ε-caprolactone copolymer include glycolic acid and lactic acid.

[0028] Moreover, the polycaprolactone used in the present invention preferably has a refractive index of 1.41 to 1.51, and more preferably 1.44 to 1.48 at 60° C. If the refractive index of the polycaprolactone is less than the lower limit or exceeds the upper limit, the difference in refractive index from a polymer blend containing an acrylic polymer and polyvinylidene fluoride in a specified ratio increases, and the transparency of the resulting resin composition at high temperatures of 70° C. or higher tends to decrease, and the visible light absorptance of the resulting resin composite material at high temperatures of 70° C. or higher tends to increase.

[0029] (Thermochromic resin composition) The thermochromic resin composition used in the present invention contains 15 to 84% by mass of the acrylic polymer, 15 to 84% by mass of the polyvinylidene fluoride, and 1 to 40% by mass of the polycaprolactone. Such a thermochromic resin composition exhibits improved transparency at high temperatures of 70° C. or higher, that is, exhibits a thermochromic effect, and the resulting resin composite material exhibits low visible light absorptance at high temperatures of 70° C. or higher.

[0030] In the thermochromic resin composition, the content of the acrylic polymer is required to be 15 to 84% by mass. If the content of the acrylic polymer is less than the lower limit or exceeds the upper limit, the thermochromic effect is not exhibited, the transparency is not improved even at high temperatures of 70°C or higher, and the obtained resin composite material has a high visible light absorptance at high temperatures of 70°C or higher. In addition, from the viewpoints that the thermochromic effect is sufficiently exhibited, the transparency is sufficiently improved at high temperatures of 70°C or higher, and the obtained resin composite material has a low visible light absorptance at high temperatures of 70°C or higher, the content of the acrylic polymer is preferably 25 to 77% by mass, more preferably 40 to 75% by mass.

[0031] In addition, in the thermochromic resin composition, the content of the polyvinylidene fluoride must be 15 to 84% by mass. If the content of the polyvinylidene fluoride is less than the lower limit or exceeds the upper limit, the thermochromic effect is not exhibited, the transparency is not improved even at high temperatures of 70°C or higher, and the obtained resin composite material has a high visible light absorptance at high temperatures of 70°C or higher. In addition, from the viewpoints that the thermochromic effect is sufficiently exhibited, the transparency is sufficiently improved at high temperatures of 70°C or higher, and the obtained resin composite material has a low visible light absorptance at high temperatures of 70°C or higher, the content of the polyvinylidene fluoride is preferably 20 to 72% by mass, more preferably 20 to 55% by mass.

[0032] Further, in the thermochromic resin composition, the content of the polycaprolactone is required to be 1 to 40% by mass. If the content of the polycaprolactone is less than the lower limit, the thermochromic property is not expressed, the transparency is not likely to decrease at a low temperature of 40°C or less, and the visible light absorptance at a low temperature of 40°C or less is low in the obtained resin composite material. On the other hand, if the content of the polycaprolactone exceeds the upper limit, the mechanical properties of the resin composition at 60°C or more are reduced. In addition, from the viewpoint that the thermochromic effect is fully expressed, the transparency is reduced at a low temperature of 40°C or less, and the visible light absorptance at a low temperature of 40°C or less is high in the obtained resin composite material, the content of the polycaprolactone is preferably 3 to 40% by mass, more preferably 5 to 40% by mass.

[0033] In addition, the thermochromic resin composition preferably has a sea-island structure including a sea phase made of a polymer blend containing the acrylic polymer and the polyvinylidene fluoride in a predetermined ratio and an island phase made of at least a part of the polycaprolactone. Due to the formation of such a sea-island structure, at low temperatures of 40° C. or less, the polycaprolactone in the island phase crystallizes to make the resin composition opaque, and the visible light absorption rate of the resulting resin composite material is high, and at high temperatures of 70° C. or more, the polycaprolactone melts to make the refractive index of the island phase similar to that of the polymer blend in the sea phase, improving transparency and exhibiting a thermochromic effect, and the visible light absorption rate of the resulting resin composite material is low.

[0034] In the sea-island structure, the size of the island phases is preferably 50 nm to 100 μm in terms of the maximum length (diameter when the island phases are circular), more preferably 100 nm to 80 μm, and particularly preferably 150 nm to 50 μm. If the size of the island phases is less than the lower limit, the thermochromic effect is not sufficiently exhibited, transparency is unlikely to decrease at low temperatures of 40° C. or less, and the visible light absorptance at low temperatures of 40° C. or less in the obtained resin composite material tends to be low. On the other hand, if the size of the island phases exceeds the upper limit, molding processability tends to decrease.

[0035] (Black coloring) The black colorant used in the present invention is at least one selected from the group consisting of black pigments and black dyes. Examples of the black pigment include carbon black, carbon nanotubes, carbon fibers, titanium black, perylene black, and oxides, composite oxides, sulfides, sulfates, carbonates, etc. of metals such as copper, iron, manganese, cobalt, chromium, nickel, zinc, calcium, and silver. Examples of the black dye include organic dyes such as anthraquinones, perinones, perylenes, azos, methines, and quinolines. Among these black colorants, carbon particles having a graphite structure are preferred from the viewpoint of affinity with the thermochromic resin composition.

[0036] In the thermochromic resin composite material of the present invention, it is preferable that 30% by mass or more (preferably 50% by mass or more, more preferably 70% by mass or more) of the black colorant is present in the island phase (phase consisting of the polycaprolactone) of the sea-island structure. This increases the visible light absorption rate at low temperatures of 40°C or less. That is, at low temperatures of 40°C or less, the polycaprolactone forms a crystalline phase, and the visible light incident on the thermochromic resin composite material is scattered by the crystalline phase. At this time, the black colorant is present in the island phase, so that visible light is efficiently absorbed.

[0037] The size and shape of the black pigment is preferably a sphere having a diameter of 5 nm to 30 μm (preferably 7 nm to 20 μm, more preferably 10 nm to 10 μm). If the size of the black pigment is less than the lower limit, the handling of the black pigment during the preparation of the thermochromic resin composite material tends to become complicated, whereas if the size of the black pigment exceeds the upper limit, the phase structure of the resin composition tends to be disturbed, and the change in visible light absorptance due to temperature tends to be small.

[0038] (Glass-based filler) The glass-based filler used in the present invention is not particularly limited, but is preferably one with a silicon dioxide purity of 90% or more. Since the glass-based filler with a silicon dioxide purity of 90% or more has a refractive index similar to that of the polymer blend containing an acrylic polymer and polyvinylidene fluoride at a predetermined ratio or the polycaprolactone at a high temperature of 70°C or more, the resin composition containing the acrylic polymer, the polyvinylidene fluoride, the polycaprolactone, and the glass-based filler improves transparency at a high temperature of 70°C or more and maintains the thermochromic effect, and the obtained resin composite material can improve scratch resistance while maintaining a low visible light absorptance at a high temperature of 70°C or more. In addition, in a resin composition containing the acrylic polymer, the polyvinylidene fluoride, the polycaprolactone, and the glass-based filler, the thermochromic effect is sufficiently maintained, transparency at a high temperature of 70° C. or higher is sufficiently improved, and the obtained resin composite material has a sufficiently low visible light absorptance at a high temperature of 70° C. or higher, so that the silicon dioxide purity of the glass-based filler is preferably 95% or higher, and more preferably 98% or higher. On the other hand, a glass-based filler having a silicon dioxide purity below the lower limit has a refractive index significantly different from that of the polymer blend and the polycaprolactone at a high temperature of 70° C. or higher, so that in a resin composition containing the acrylic polymer, the polyvinylidene fluoride, the polycaprolactone, and the glass-based filler, the thermochromic effect is not maintained, transparency at a high temperature of 70° C. or higher is reduced, and the obtained resin composite material tends to have a high visible light absorptance at a high temperature of 70° C. or higher.

[0039] The glass-based filler preferably has a refractive index of 1.40 to 1.50, and more preferably 1.44 to 1.48 at 60° C. If the refractive index of the glass-based filler is less than the lower limit or exceeds the upper limit, the transparency of the resin composition containing the acrylic polymer, the polyvinylidene fluoride, the polycaprolactone, and the glass-based filler at high temperatures of 70° C. or higher tends to decrease, and the visible light absorptance of the resulting resin composite material at high temperatures of 70° C. or higher tends to increase.

[0040] The size and shape of the glass-based filler are preferably spherical with a diameter of 100 nm to 2 mm (preferably 200 nm to 1.5 mm, more preferably 500 nm to 1 mm) or fibrous with a fiber diameter of 100 nm to 2 mm (preferably 200 nm to 1.5 mm, more preferably 500 nm to 1 mm) and a fiber length of 100 μm to 50 mm (preferably 200 μm to 30 mm, more preferably 300 μm to 10 mm). If the size of the glass-based filler is less than the lower limit, handling tends to be difficult, whereas if it exceeds the upper limit, the moldability of the resin composition tends to decrease.

[0041] (Thermochromic resin composite material) The thermochromic resin composite material of the present invention contains 0.0005 to 0.03 parts by mass of the black colorant relative to 100 parts by mass of the thermochromic resin composition. This thermochromic resin composite material changes the visible light absorptance depending on the temperature, and the visible light absorptance is low at high temperatures of 70°C or higher, and high at low temperatures of 40°C or lower. For example, in the case of a plate-shaped thermochromic resin composite material having a thickness of 0.5 mm, the difference in visible light absorptance between low temperatures of 40°C or lower and high temperatures of 70°C or higher is 10% or more. On the other hand, if the content of the black colorant is less than the lower limit, the visible light absorptance does not improve (particularly at low temperatures of 40°C or lower), and on the other hand, if the content of the black colorant exceeds the upper limit, the visible light absorptance becomes too high, making it difficult for the visible light absorptance to change with temperature. From the viewpoint of increasing the difference in visible light absorptance between a low temperature of 40°C or less and a high temperature of 70°C or more, the content of the black colorant is preferably 0.001 to 0.025 parts by mass, more preferably 0.002 to 0.020 parts by mass, and particularly preferably 0.003 to 0.015 parts by mass, relative to 100 parts by mass of the thermochromic resin composition.

[0042] In addition, in the thermochromic resin composite material of the present invention, it is preferable that 50 parts by mass or less of a glass-based filler is further contained relative to 100 parts by mass of the thermochromic resin composition. By containing the glass-based filler, the scratch resistance of the obtained resin composite material can be improved, and the radiative cooling ability of the thermochromic resin composite material can be improved. On the other hand, if the content of the glass-based filler exceeds the upper limit, the molding processability tends to decrease. In addition, from the viewpoint of the scratch resistance, radiative cooling ability, and molding processability of the obtained resin composite material, the content of the glass-based filler is more preferably 5 to 40 parts by mass, particularly preferably 10 to 30 parts by mass, relative to 100 parts by mass of the thermochromic resin composition.

[0043] There is no particular limitation on the method for producing such a thermochromic resin composite material, and known kneading methods such as melt kneading can be adopted, but from the viewpoint of making the black colorant exist in the island phase made of the polycaprolactone and dispersing the island phase uniformly, first, the black colorant and the polycaprolactone are dry blended, and then the resulting mixture is kneaded (preferably melt kneaded) to prepare a master batch, and then the acrylic polymer, the polyvinylidene fluoride, the polycaprolactone, the master batch, and the glass-based filler as necessary are dry blended, and then the resulting mixture is kneaded (preferably melt kneaded) to produce the thermochromic resin composite material of the present invention. Furthermore, this thermochromic resin composite material may be molded into a desired shape.

[0044] [Laminate] Next, the laminate of the present invention will be described. The laminate of the present invention comprises a member made of the thermochromic resin composite material of the present invention and a metal film having a visible light reflectance of 70% or more that is disposed on at least a part of one side of the member.

[0045] (Components made of thermochromic resin composite materials) The member made of the thermochromic resin composite material used in the present invention is obtained by molding the thermochromic resin composite material of the present invention into a desired shape. The shape of the member made of the thermochromic resin composite material is not particularly limited, and examples thereof include a plate shape such as a square plate or a disk, and a flexible film shape.

[0046] When the member made of the thermochromic resin composite material is a plate-shaped member, its thickness is preferably 0.01 to 3.0 mm, more preferably 0.05 to 2.5 mm, and particularly preferably 0.1 to 2.0 mm. If the thickness of the plate-shaped member is less than the lower limit, the change in visible light absorptance due to temperature tends to be small, whereas if the thickness of the plate-shaped member exceeds the upper limit, the temperature responsiveness of the visible light absorptance tends to decrease.

[0047] (Metal Film) The metal film used in the present invention has a visible light (particularly, a wavelength of 589 nm) reflectance of 70% or more. When the visible light reflectance of the metal film is less than the lower limit, the change in visible light absorptance due to temperature becomes small. In addition, the visible light reflectance of the metal film is preferably 80% or more, more preferably 85% or more, and particularly preferably 90% or more.

[0048] Examples of such metal films include silver foil (visible light (wavelength 589 nm) reflectance: 94%) and aluminum foil (visible light (wavelength 589 nm) reflectance: 81%).

[0049] In the metal film, the content (purity) of the main component metal (for example, silver in the case of silver foil, aluminum in the case of aluminum foil) is preferably 70 mass % or more, more preferably 75 mass % or more, and particularly preferably 80 mass % or more. If the content (purity) of the main component metal is less than the lower limit, the change in visible light absorptance due to temperature tends to be small.

[0050] The thickness of the metal film is preferably 50 nm to 100 μm, more preferably 75 nm to 50 μm, and particularly preferably 100 nm to 25 μm. If the thickness of the metal film is less than the lower limit, the change in visible light absorptance due to temperature tends to be small, whereas if the thickness of the plate-like member exceeds the upper limit, the flexibility of the member tends to decrease.

[0051] (Laminate) The laminate of the present invention comprises a member made of the thermochromic resin composite material and the metal film disposed on at least a part of one side of the member. The reflectance of visible light in this laminate changes with temperature, and the reflectance of visible light is high at high temperatures of 70° C. or higher and is low at low temperatures of 40° C. or lower. For example, in the case of a laminate comprising a plate-shaped member made of the thermochromic resin composite material with a thickness of 0.5 mm, the difference in reflectance of visible light (wavelength 589 nm) between low temperatures of 40° C. or lower and high temperatures of 70° C. or higher is 10% or more.

[0052] There is no particular limitation on the method for producing such a laminate. For example, a member made of the thermochromic resin composite material and the metal film may be superimposed on each other, and then thermocompression bonded by press molding or the like, or the metal film may be vapor-deposited onto the surface of the member made of the thermochromic resin composite material. EXAMPLES

[0053] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. The raw materials used in the examples and comparative examples are shown below.

[0054] (raw materials) PMMA: polymethyl methacrylate ("Parapet G grade" manufactured by Kuraray Co., Ltd., refractive index: 1.492 (23°C), 1.489 (60°C)). PVDF: polyvinylidene fluoride (Aldrich, catalog number: 427144, refractive index: 1.42 (23°C)). PCL: polycaprolactone (Aldrich, catalog number: 440744, refractive index: 1.46 (50°C)). Black pigment: carbon black (Aldrich, catalog number: 05-1530-5-500G-J, particle size: 24 nm). Black dye: oil-soluble azine dye (a mixture of linear alkylbenzene sulfonic acid and oil-soluble anthraquinone dye, "NUBIAN BLACK PC-8550" manufactured by Orient Chemical Industry Co., Ltd.). SiO2: Silicon dioxide ("SO-C6" manufactured by Admatechs Co., Ltd., silicon dioxide purity: 99% or more, particle size: 1.8 to 2.3 μm). Silver foil: Kenis Co., Ltd., catalog number: 68381066, thickness: 400 nm.

[0055] Example 1 First, PCL (100 parts by mass) and black pigment (0.44 parts by mass) were dry-blended, and the resulting mixture was then placed in a small tabletop kneader (Haake's "Minilab") and kneaded at 170°C for 5 minutes to prepare a master batch (MB1).

[0056] Next, PMMA, PVDF, PCL, the master batch (MB1), and SiO2 were dry-blended to a mixture of 52 parts by mass of PMMA, 28 parts by mass of PVDF, 20 parts by mass of PCL, 0.01 parts by mass of black pigment, and 25 parts by mass of SiO2. The resulting mixture was then placed in a small benchtop kneader (Haake's "Minilab") and kneaded at 220°C for 5 minutes to prepare a resin composite material.

[0057] The obtained resin composite material was press molded at a temperature of 220°C and a pressure of 6 MPa for 30 seconds using a bench press to produce a flat plate of 50 mm x 50 mm x 0.5 mm.

[0058] (Examples 2 to 6) A resin composite material was prepared in the same manner as in Example 1, except that the contents of PMMA, PVDF, PCL, black pigment, and SiO2 were changed to the amounts shown in Table 1, and a flat plate of 50 mm x 50 mm x 0.5 mm was further produced.

[0059] Example 7 Except for using a black dye (0.44 parts by mass) instead of the black pigment, a master batch (MB2) was prepared in the same manner as in Example 1. Except for using this master batch (MB2) instead of the master batch (MB1), a resin composite material was prepared in the same manner as in Example 3, and a flat plate of 50 mm × 50 mm × 0.5 mm was produced.

[0060] Comparative Example 1 PMMA (65 parts by mass), PVDF (35 parts by mass), black pigment (0.005 parts by mass), and SiO2 (25 parts by mass) were dry-blended, and the resulting mixture was placed in a small tabletop kneader (Haake's "Minilab") and kneaded for 5 minutes at 220°C to prepare a resin composite material. A 50 mm x 50 mm x 0.5 mm flat plate was produced in the same manner as in Example 1, except that this resin composite material was used instead of the resin composite material prepared in Example 1.

[0061] Comparative Example 2 A resin composite material was prepared in the same manner as in Example 1, except that the contents of PMMA, PVDF, PCL, black pigment, and SiO2 were changed to the amounts shown in Table 1, and a flat plate of 50 mm x 50 mm x 0.5 mm was further produced.

[0062] <Light absorption rate> A temperature controller was installed in the sample chamber of a haze meter ("HGM-3DP" manufactured by Suga Test Instruments Co., Ltd.), and the total light transmittance [%] of the flat plate was measured at each temperature (25 to 100°C) using this haze meter. From the total light transmittance obtained, the following formula: Light absorption rate [%] = 100 - total light transmittance [%] The light absorption rate [%] was calculated by the above method. The results are shown in Table 1.

[0063] [Table 1]

[0064] As shown in Table 1, the resin composite materials (Examples 1 to 7) containing acrylic polymer, polyvinylidene fluoride, polycaprolactone, and black colorant in specified ratios had a difference in visible light absorptance of 10% or more between room temperature (25°C) and high temperature (80°C), and were confirmed to be thermochromic resin composite materials whose visible light absorptance changes with temperature.

[0065] On the other hand, in the resin composite material not containing polycaprolactone (Comparative Example 1), no change in visible light absorptance due to temperature was observed since no light scattering source was contained.

[0066] Moreover, in the resin composite material (Comparative Example 2) containing a black colorant exceeding a predetermined amount, the visible light absorptance was too high, and no change in the visible light absorptance due to temperature was observed.

[0067] Example 8 The flat plate prepared in Example 1 was placed on the silver foil and then press molded for 30 seconds at a temperature of 220°C and a pressure of 6 MPa using a bench press to produce a laminate in which the silver foil was thermocompressed onto the entire back surface of the flat plate.

[0068] Example 9 A laminate was produced in the same manner as in Example 8, except that the flat plate produced in Example 3 was used instead of the flat plate produced in Example 1, and a silver foil was thermocompression-bonded to the entire back surface of the flat plate.

[0069] Example 10 A laminate was produced in the same manner as in Example 8, except that the flat plate produced in Example 5 was used instead of the flat plate produced in Example 1, and a silver foil was thermocompression-bonded to the entire back surface of the flat plate.

[0070] Example 11 A laminate was produced in the same manner as in Example 8, except that the flat plate produced in Example 7 was used instead of the flat plate produced in Example 1, and a silver foil was thermocompression-bonded to the entire back surface of the flat plate.

[0071] Comparative Example 3 PMMA (52 parts by mass), PVDF (28 parts by mass), PCL (20 parts by mass), and SiO2 (25 parts by mass) were dry-blended, and the resulting mixture was placed in a small tabletop kneader (Haake's "Minilab") and kneaded at 220°C for 5 minutes to prepare a resin composite material. A 50 mm x 50 mm x 0.5 mm flat plate was prepared in the same manner as in Example 1, except that this resin composite material was used instead of the resin composite material prepared in Example 1, and a laminate in which silver foil was thermocompression-bonded to the entire back surface of the flat plate was prepared in the same manner as in Example 8, except that this flat plate was used instead of the flat plate prepared in Example 1.

[0072] Comparative Example 4 A laminate was produced in the same manner as in Example 8, except that the flat plate produced in Comparative Example 1 was used instead of the flat plate produced in Example 1, and a silver foil was thermocompression-bonded to the entire back surface of the flat plate.

[0073] Comparative Example 5 A laminate was produced in the same manner as in Example 8, except that the flat plate produced in Comparative Example 2 was used instead of the flat plate produced in Example 1, and a silver foil was thermocompression-bonded to the entire back surface of the flat plate.

[0074] <Light reflectance> A rubber heater was placed on the back surface of the obtained laminate (the surface of the silver foil), and the light reflectance [%] of the laminate was measured by irradiating the surface of the laminate (the surface without the silver foil) with light of 589 nm wavelength using an ultraviolet-visible spectrophotometer (Shimadzu Corporation's "UV-3600") equipped with an integrating sphere at 25° C. and 70° C. The results are shown in Table 2.

[0075] [Table 2]

[0076] As shown in Table 2, it was confirmed that the laminated plates (Examples 8 to 11) in which silver foil was thermocompressed onto the entire back surface of a flat plate made of a resin composite material containing acrylic polymer, polyvinylidene fluoride, polycaprolactone, and black colorant in a specified ratio had improved light reflectance at high temperatures (70°C) compared to room temperature (25°C).

[0077] On the other hand, the laminated plate in which silver foil was thermocompression-bonded to the entire back surface of a flat plate made of a resin composite material not containing a black colorant (Comparative Example 3), the laminated plate in which silver foil was thermocompression-bonded to the entire back surface of a flat plate made of a resin composite material not containing polycaprolactone (Comparative Example 4), and the laminated plate in which silver foil was thermocompression-bonded to the entire back surface of a flat plate made of a resin composite material containing more than a specified amount of black colorant (Comparative Example 5) all showed very small changes in light reflectance with temperature.

[0078] <Heat generated by sunlight> An outdoor test apparatus was prepared using a rubber heater and a data logger. The laminate prepared in Example 9 was placed in this outdoor test apparatus. The amount of heat input to the heater was measured at 45° C. and 70° C. when the surface of the laminate (the surface without the silver foil) was not irradiated with sunlight and when it was irradiated with sunlight, and the amount of heat input was calculated using the following formula: Heat generation due to sunlight = Heat input to heater when exposed to sunlight - Heat input to heater when not exposed to sunlight The amount of heat generated by sunlight was calculated using the above method. The results are shown in Table 3.

[0079] [Table 3]

[0080] As shown in Table 3, the amount of heat generated by sunlight in the laminate produced in Example 9 changed between 45°C and 70°C, indicating that the laminate is a composite material in which the amount of heat generated by sunlight changes autonomously with temperature changes. [Industrial Applicability]

[0081] As described above, according to the present invention, it is possible to obtain a resin composite material that exhibits low visible light absorptance at high temperatures of 70° C. or higher and high visible light absorptance at low temperatures of 40° C. or lower. Furthermore, by providing a metal film on one side of a member made of such a resin composite material, it is possible to obtain a laminate that exhibits high light reflectance at high temperatures of 70° C. or higher and low light reflectance at low temperatures of 40° C. or lower.

[0082] When such a laminate of the present invention is irradiated with sunlight, when the temperature is low, the solar absorptance is high (the visible light reflectance is low), so that the amount of heat generated by the sunlight is large, whereas when the temperature is high, the solar absorptance is low (the visible light reflectance is high), so that the amount of heat generated by the sunlight is small.

[0083] Therefore, the laminate of the present invention can be applied as an autonomous temperature control material in which the amount of heat generated by sunlight changes with changes in the outside air temperature, and is useful as a laminate used in, for example, buildings such as houses, factories, warehouses, and transport vehicles such as automobiles and trains. Moreover, by attaching such a laminate to the surface of an adherend (for example, a roof or wall surface) so that the adherend is disposed on the metal film side of the laminate, when the temperature is low, the laminate generates heat due to sunlight, making it possible to heat the adherend by this heat generation, and when the temperature is high, sunlight is reflected by the laminate, making it possible to suppress heating of the adherend by sunlight.

Claims

1. A thermochromic resin composition containing 15 to 84 mass% polymethyl methacrylate, 15 to 84 mass% polyvinylidene fluoride, and 1 to 40 mass% polycaprolactone, and 0.0005 to 0.03 parts by mass of at least one black colorant selected from the group consisting of black pigments and black dyes, relative to 100 parts by mass of the thermochromic resin composition A thermochromic resin composite material comprising:

2. 2. The thermochromic resin composite material according to claim 1, further comprising 50 parts by mass or less of a glass-based filler relative to 100 parts by mass of the thermochromic resin composition.

3. 3. The thermochromic resin composite material according to claim 2, wherein the glass-based filler has a silicon dioxide purity of 90% or more.

4. 2. The thermochromic resin composite material according to claim 1, wherein the black colorant is carbon particles having a graphite structure.

5. 10. A laminate comprising: a member made of the thermochromic resin composite material according to claim 1; and a metal film having a visible light reflectance of 70% or more, disposed on at least a portion of one surface of said member.

Citation Information

Patent Citations

  • Temperature sensitive glass material

    JP1990102043A

  • Thermochromic resin composition

    JP1994192525A

  • Production method for thermochromic material, and dimmer using the same

    JP2001354952A

  • Thermochromic material

    JP2018095801A

  • Thermochromic material

    JP2019031606A